DIPLOMASI EMPATIK: PEREMPUAN DAN STRATEGI MEDIASI DALAM KONFLIK KOMUNAL - Najmuddin, Muhammad; Siti Rabiatul Adawiyah (Pusat Studi Gender dan Anak, UIN Palu, 2025)
This study explores the strategic role of women as mediators in communal conflicts in Sigi Regency, Central Sulawesi. Using a qualitative case study approach, the research investigates how women employ empathetic communication strategies rooted in local cultural and spiritual values to facilitate reconciliation processes in post-conflict communities. Data were collected through in-depth interviews, participatory observations, and document analysis involving women mediators, religious and traditional leaders, and conflict-affected community members. The findings reveal three main aspects: first, women play a substantive and proactive role in initiating dialogue and restoring broken social relationships; second, their mediation strategies integrate empathetic communication, religious-spiritual values, and cultural symbols to create a safe space for peacebuilding; third, despite their significant contributions, women often face structural and symbolic barriers that limit formal recognition of their roles. The study concludes that empathetic diplomacy practiced by women offers a contextually relevant and sustainable model for grassroots conflict resolution. This research contributes to the discourse on gender, peace, and communication by highlighting the transformative power of women’s agency and the importance of culturally rooted approaches in conflict mediation.